A NOTE ON THE MAGELLANIC CLOUDS - MENDOZA, EUGENIO (UNAM, Instituto de Astronomía, CD MEXICO, DF, MEX, 1970)
Narrow band photometry has been obtained for 36 stars in the Magellanic Clouds. The observations were calibrated with galactic supergiants to determine the distance to both Clouds. The results for the LMC are excellent, while not so for the SMC. The latte
BOL OBS TONAN TACUB
Keywords: NOTE, MAGELLANIC CLOUDS; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; GALAXIAS